Sosialisasi Pengenalan Reksadana Sebagai Wadah Investasi Bagi Ibu Rumah Tangga - Tiar Lina Situngkir (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2019)
Community service activities suggestions for providing information on mutual fund investments that can be a place for housewives in middle-class communities in the Galuh Mas Arisan community in Karawang can be an alternative to allocating surplus funds available for more useful investments by storing them. in mutual funds and getting back or yields that increase income and financial well-being in the family. Delivered by presentations and explaining mutual fund definition, forms of mutual funds, types - mutual funds, and places to buy mutual funds. Incommunity serviceactivities carried out almost all participants who had heard the word mutual funds did not understand and understand the meaning of mutual funds, but there is a mother who had made mutual fund purchase transactions. The conclusions of this activity are participants who at first did not consider mutual funds after this activity get more knowledge about mutual funds and added insight into investments that could be carried out in the future. Keywords: housewive, investment, mutual fund